1990
DOI: 10.1002/jso.2930430411
|View full text |Cite
|
Sign up to set email alerts
|

Complications following surgery for cancer of the larynx and pyriform fossa

Abstract: The hospital records of patients undergoing major surgery for cancer of the larynx and hypopharynx at the Tata Memorial Hospital, Bombay, from 1981 to 1985 were reviewed. Different variables were correlated with the incidence of major complications and were analysed to find out significant factors contributing to increased complication rates. Complications included wound infection, pharyngocutaneous fistulae, flap necrosis, carotid blowout, and neo-esophageal stenosis. Postoperative deaths and delayed fataliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
53
2

Year Published

1994
1994
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 24 publications
8
53
2
Order By: Relevance
“…Some retrospective studies have reported an increased incidence of wound and systemic complications for salvage laryngectomy after RT or CRT (9,10,11,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some retrospective studies have reported an increased incidence of wound and systemic complications for salvage laryngectomy after RT or CRT (9,10,11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Sarkar et al reported that prior irradiation significantly affected the incidence of PCF, 58% for irradiated patients and 21% for non-irradiated patients, respectively (12). A meta-analysis of post-laryngectomy PCF showed that pre-operative radiotherapy increased the risk of PCF formation, and the severity and duration of fistula were greater than those without pre-operative radiotherapy (14).…”
Section: Discussionmentioning
confidence: 99%
“…1 Adjuvant and neoadjuvant chemotherapy has been added to various multimodality approaches. [1][2][3][4][5][6][7] Concurrent chemotherapy and radiation therapy has also been proposed. [8][9][10] Advantages of this approach include the independent antineoplastic activity of both treatments, the radiotherapeutic potentiation exerted by several chemotherapeutic agents, the possibility that systemic chemotherapy may decrease micrometastatic spread, and the relatively short duration of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…8 Although these aggressive organ preservation protocols have produced encouraging results, an increased incidence of surgical complications in patients who require surgery for persistent or recurrent disease has been reported. Curative radiotherapy and induction chemotherapy followed by definitive radiotherapy result in complication rates for salvage operations of 37% to 74% [2][3][4][5]11 and 46% to 100%, 6,7,12,13 respectively. Induction chemotherapy and chemoradiotherapy for organ preservation are used with the primary goal being the elimination of extensive surgery in hopes of maintaining normal speech and swallowing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation